2020
DOI: 10.3390/rs12223726
|View full text |Cite
|
Sign up to set email alerts
|

Influence of LiDAR Point Cloud Density in the Geometric Characterization of Rooftops for Solar Photovoltaic Studies in Cities

Abstract: The use of LiDAR (Light Detection and Ranging) data for the definition of the 3D geometry of roofs has been widely exploited in recent years for its posterior application in the field of solar energy. Point density in LiDAR data is an essential characteristic to be taken into account for the accurate estimation of roof geometry: area, orientation and slope. This paper presents a comparative study between LiDAR data of different point densities: 0.5, 1, 2 and 14 points/m2 for the measurement of the area of roof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The Apple LiDAR point clouds are denser than those from sUAS SfM, with the scanner generating in total 83,179,489 points in July and 63,984,235 points in September, compared to the sUAS SfM point clouds which had 6,976,757 points in July and 7,179,555 points in September (Table 3). The higher density of the Apple LiDAR point clouds allows for a more detailed representation of the survey area [34]. This is particularly true in areas such as the foredunes where low elevation grasses occur on top of the bare sand, which is a documented challenge for rendering accurate bare earth DEMs using sUAS surveying methods.…”
Section: Discussionmentioning
confidence: 99%
“…The Apple LiDAR point clouds are denser than those from sUAS SfM, with the scanner generating in total 83,179,489 points in July and 63,984,235 points in September, compared to the sUAS SfM point clouds which had 6,976,757 points in July and 7,179,555 points in September (Table 3). The higher density of the Apple LiDAR point clouds allows for a more detailed representation of the survey area [34]. This is particularly true in areas such as the foredunes where low elevation grasses occur on top of the bare sand, which is a documented challenge for rendering accurate bare earth DEMs using sUAS surveying methods.…”
Section: Discussionmentioning
confidence: 99%
“…The National Geographic Institute (IGN) in Spain offers highly accurate and updated LiDAR data of the entire Spanish territory, captured periodically under the National Plan for Territory Observation (Plan Nacional de Observación del Territorio—PNOT) [ 38 ]. Previous studies have demonstrated the applicability of these LiDAR data in urban environments in Spain [ 39 , 40 , 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…The present research had the following methodological steps (Figure 1 nighttime light satellite imagery [50][51][52], among others. In solar energy, many studies use remote sensing images, such as solar energy estimates [53][54][55][56], solar power plant site selection [57][58][59][60][61][62], PV potential on building rooftops [63][64][65][66], and area estimation [67,68].…”
Section: Methodsmentioning
confidence: 99%
“…Remote sensing data (aerial photography and satellite imagery) enable inspection periodically, and have been widely used in the electrical sector for effective maintenance of electrical lines [39][40][41], thermal monitoring from nuclear power plants [42][43][44][45], environmental changes from hydroelectric dams [46][47][48][49], and energy consumption using nighttime light satellite imagery [50][51][52], among others. In solar energy, many studies use remote sens-ing images, such as solar energy estimates [53][54][55][56], solar power plant site selection [57][58][59][60][61][62], PV potential on building rooftops [63][64][65][66], and area estimation [67,68].…”
Section: Introductionmentioning
confidence: 99%